Student Interest in Continuing Education to Advanced School - Lolla Sintyani; Marjohan Marjohan (Universitas Negeri Padang, 2021)
Interest is an impetus that creates a great desire in students to continue their education to secondary school. Interest consist of two aspects, namely cognitive aspects and affective aspects. This study aims to see (1) a description of student interest in continuing education to secondary school seen from the cognitive aspect, namely with regard to the need for information and interest in secondary school, (2) the description of student interest in continuing education to secondary school is seen from the affective aspect, namely with regard to parental attention and support, teacher attention and support, and peer attention and support. This type of research is a descriptive study using quantitative methods. The study population was 238 students who were in class IX at SMP Negeri 15 Padang who were registered in the 2020/2021 academic year, with a total sample of 149 students who were selected using proportional random sampling technique.The research findings reveal that (1) students interest in continuing education to secondary school seen from the cognitive aspect is in the medium category with a percentage 37,58%, (2) student interest in continuing education to secondary school seen from the affective aspect is in the medium category with a percentage 43,62%.